PERSAHABATAN DALAM NOVEL CHARLOTTEâ€™S WEB KARYA E.B. WHITE - Massie, Rezky Juan; Marentek, Andriyani; Wantasen, Isnawaty L. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â  AbstractÂ Â Â  This research entitled â€œPersahabatan dalam Novel Charlotteâ€™s Web karya E.B. White (1950)â€ is written to fulfill the requirements of accomplishing bachelorâ€™s degree in English Department, Faculty of Humanities, Sam Ratulangi University. The focus of this investigation is to find the friendship portrayed in the novel Charlotteâ€™s Web. This research particularly investigates the types of friendship and the portrayals of the friendship in the novel. The writer used the theory from W. D. Ross (1999) to identify and classify the data and the theory from Robert Stanton (1965) to analyze the friendship portrayed in the novel Charlotteâ€™s Web. The results of this research show 3 (three) types of friendship and 4 (four) types of characters portrayed. The three types of friendship are: 1) friendship of utility, 2) friendship of pleasure, and 3) friendship of the good. The two types of character portrayals are the friendships according to: 1) characterâ€™s speech and 2) characterâ€™s action.Keywords: Friendship, Types of friendship, Character, Novel, Theory of Novel.